N-cadherin overexpression enhances the reparative potency of human-induced pluripotent stem cell-derived cardiac myocytes in infarcted mouse hearts. Issue 3 (26th July 2019) - Lou, Xi; Zhao, Meng; Fan, Chengming; Fast, Vladimir G; Valarmathi, Mani T; Zhu, Wuqiang; Zhang, Jianyi
Abstract: Aims: In regenerative medicine, cellular cardiomyoplasty is one of the promising options for treating myocardial infarction (MI); however, the efficacy of such treatment has shown to be limited due to poor survival and/or functional integration of implanted cells. Within the heart, the adhesion between cardiac myocytes (CMs) is mediated by N-cadherin (CDH2) and is critical for the heart to function as an electromechanical syncytium. In this study, we have investigated whether the reparative potency of human-induced pluripotent stem cell-derived cardiac myocytes (hiPSC-CMs) can be enhanced through CDH2 overexpression. Methods and results: CDH2-hiPSC-CMs and control wild-type (WT)-hiPSC-CMs were cultured in myogenic differentiation medium for 28 days. Using a mouse MI model, the cell survival/engraftment rate, infarct size, and cardiac functions were evaluated post-MI, at Day 7 or Day 28. In vitro, conduction velocities were significantly greater in CDH2-hiPSC-CMs than in WT-hiPSC-CMs. While, in vivo, measurements of cardiac functions: left ventricular (LV) ejection fraction, reduction in infarct size, and the cell engraftment rate were significantly higher in CDH2-hiPSC-CMs treated MI group than in WT-hiPSC-CMs treated MI group. Mechanistically, paracrine activation of ERK signal transduction pathway by CDH2-hiPSC-CMs, significantly induced neo-vasculogenesis, resulting in a higher survival of implanted cells. Conclusion: Collectively, these data suggest that CDH2 overexpression enhances not only the survival/engraftment of cultured CDH2-hiPSC-CMs, but also the functional integration of these cells, consequently, the augmentation of the reparative properties of implanted CDH2-hiPSC-CMs in the failing hearts. Graphical Abstract: